Study and Determination of the Order of Chlorine Reaction with water and the appropriate kinetic model for Chlorine decay in the drinking water supply network in Latakia City - مي الفريد ناصر; رائد جعفر; هيثم جناد; عادل عوض (Latakia University Journal -Engineering Sciences Series, 2022)
This study aimed to determine the order of the reaction of chlorine with water in order to reach at the appropriate kinetic model to study the decay of chlorine in the drinking water network and to determine the chlorine decay coefficient (Kb) .Twelve sampling points were selected distributed on the main lines of the drinking water supply network in Lattakia city, Water samples were collected from the specified sampling points at a rate of once a month, as the study lasted for seven months from June (2021) until December (2021) which the concentrations of free residual chlorine were measured at each sampling point with, the adoption of initial time of measurement being the time of sample collecting. Then the concentrations of residual free chlorine were measured with an hour difference each measurement for each sampling point Then, the graph of the relationship between the concentrations of free residual chlorine,and its logarithm and its reciprocal was drawn against the measurement time over a period of (24) hours until the value of the concentration of free residual chlorine approaches zero.Based on the value of the correlation coefficient (R2) of the previous relationships for each sampling point during the studied months.The accuracy of the correlation was determined and the value of the strongest (R2) was chosen. The value of (R2) was the strongest for the logarithmic relationship of chlorine concentrations against the measurement time for all sampling points during the studied months , and therefore the order of the reaction was of the first order, and based on the order of the reaction, The kinetic model that describes the decay rate of chlorine in drinking water, which is a first order model, was chosen